Challenges and Legal Strategies of Indonesia in Global Trade Agreements in the Era of Fragmentation - Yatini; Kandi Kirana Larasati; Yaakub, Aliah Hana binti (LIBERATICA, 2025)
The escalation of global trade wars and the growing fragmentation of the international economic order have prompted countries, including Indonesia, to re-evaluate their legal positions and strategic approaches in international trade agreements. In the aftermath of the U.S.–China trade conflict, shifting geopolitical dynamics and economic uncertainty have posed new challenges for Indonesia in balancing its commitment to global economic liberalization with the need to safeguard domestic interests. This article examines how Indonesia adapts its trade law framework across bilateral, regional, and multilateral platforms such as CEPA, RCEP, and CPTPP. Using a normative-qualitative approach and comparative legal analysis, the study explores international legal instruments and national policies, including the Trade Law and Investment Law. The findings indicate structural tension between Indonesia’s international liberalization commitments and domestic protectionist needs, compounded by weak cross-sectoral policy harmonization and underutilization of trade remedies. These shortcomings diminish legal certainty and reduce the effectiveness of business protection mechanisms. This article argues for regulatory reform based on regulatory agility, enhanced institutional capacity in trade agreement negotiations, and the development of an integrated national legal strategy. Such efforts are essential to strengthening Indonesia’s bargaining position and resilience in the face of increasingly fragmented and volatile global trade systems. The study contributes to the discourse on how developing economies navigate legal complexities in global trade governance